Long‐term modeling of the forest–grassland ecotone in the French Alps: implications for land management and conservation. Issue 5 (1st July 2014) - Carlson, Bradley Z.; Renaud, Julien; Biron, Pierre Eymard; Choler, Philippe
Abstract : Understanding decadal‐scale land‐cover changes has the potential to inform current conservation policies. European mountain landscapes that include numerous protected areas provide a unique opportunity to weigh the long‐term influences of land‐use practices and climate on forest–grassland ecotone dynamics. Aerial photographs from four dates (1948, 1978, 1993, and 2009) were used to quantify the extent of forest and grassland cover at 5‐m resolution across a 150‐km 2 area in a protected area of the southwestern French Alps. The study area included a grazed zone and a nongrazed zone that was abandoned during the 1970s. We estimated time series of a forestation index (FI) and analyzed the effects of elevation and grazing on FI using a hierarchical linear mixed effect model. Forest extent (composed primarily of mountain pine, Pinus uncinata ) expanded from 50.6 km 2 in 1948 to 85.5 km 2 in 2009, i.e., a 23% increase in relative cover at the expense of grassland communities. Over the sixty‐year period, the treeline rose by 118 m, from 1564 to 1682 m. Rapid forest expansion within the nongrazed zone followed the cessation of logging activities and was likely accelerated by climate warming during the 1980s. Within the grazed zone, the maintained presence of sheep did not fully counteract mountain pine expansion and led to highly contrasting rates of land‐cover change based on the location of shepherds' cabins and water sources. Projections of FI for 2030 showed remnant patches of intensively used grasslands interspersed in a densely forested matrix. Our analysis of mountain land‐cover dynamics provided strong evidence for forest encroachment into grassland habitat despite consistent grazing pressure. This pattern may be attributed to the disappearance of traditional land‐use practices such as shrub burning and removal. Our findings prompt land managers to reconsider their initial conservation priority (i.e., the protection of a renowned mountain pine forest) and to implement proactive management strategies in order to preserve landscape heterogeneity and biological diversity. Projecting historical trends in the forest–grassland ecotone to 2030 provides stakeholders with a policy relevant tool for near‐term land management.